Revision of Cervonema Wieser, 1954 and Laimella Cobb, 1920 (Nematoda: Comesomatidae) with descriptions of two species from East Sea, Korea - Hong, Jung-Ho; Tchesunov, Alexei V.; Lee, Wonchoel (Zootaxa, 2016)
One new and one known species of the family Comesomatidae Filiepjev, 1918 were collected from marine sediments in the East Sea, Korea. Cervonema donghaensis sp. nov. is related to C. proximamphidum Tchesunov, 2000 and C. chilensis Chen & Vincx, 2000 but differs from them by the presence of the gubernaculum and by having outer labial setae and cephalic setae of unequal length. It differs from C. proximamphidum by having a rather shorter tail and the shape of the posterior widening of the pharynx, which has distinct muscular striation. Cervonema donghaensis sp. nov. differs from C. chilensis in body length, higher de Man’s ratio c, and having a shorter cylindrical portion of the tail. Cervonema deltensis Hope & Zhang 1995 is considered as a junior synonym of C. tenuicauda (Schuurmans Stekhoven, 1950) Wieser, 1954. Specimens of Laimella filipjevi Jensen, 1979 from East Sea, Korea largely agree with the original description of Jensen (1979) of nematodes from the Western Baltic Sea, except for slight differences in length of cephalic setae and spicules. It also coincides well with the redescription of L. filipjevi by Tchesunov (2000) based on specimens from the White Sea. Pictorial keys for the identification of valid species in the genera Cervonema Wieser, 1954 and Laimella Cobb, 1920 are given.